A shot in the dark for conservation: Evidence of illegal commerce in endemic and threatened species of elasmobranch at a public fish market in southern Brazil - Cruz, Vanessa Paes da [UNESP]; Adachi, Aisni Mayumi Corrêa de Lima [UNESP]; Ribeiro, Giovana da Silva [UNESP]; Oliveira, Pablo Henrique de [UNESP]; Oliveira, Cláudio de [UNESP]; Oriano Junior, Rinaldo; Freitas, Renato Hajenius Aché de; Foresti, Fausto [UNESP] (Wiley, 2021)
The illegal sale of endangered elasmobranchs has been recorded in a number of different Brazilian states, where sharks and rays are being marketed primarily as ‘cação’ or ‘viola’. Brazil is ranked among the top 10 nations worldwide that harvest most sharks, causing an immeasurable impact on the local elasmobranch populations. The present study applied the DNA barcoding technique, based on the cytochrome C oxidase subunit I gene, for the molecular identification of the elasmobranch species sold as processed products under the generic names of ‘cação’, ‘mangona’, ‘azul’, ‘cambeva’, ‘fiuso’ and ‘lombo preto’, in the fish market of the city of Florianópolis, capital of the state of Santa Catarina, Brazil. Nine elasmobranch species were identified in the 56 samples analysed, including six sharks and three rays, representing six families, the Carcharhinidae, Sphyrnidae, Squatinidae, Arhynchobatidae, Myliobatidae and Gymnuridae. Prionace glauca, identified in more than half (56%) of the samples analysed, is listed as Near Threatened by the International Union for the Conservation of Nature. Six species identified in the present study, Sphyrna zygaena, Sphyrna lewini, Squatina guggenheim, Carcharhinus signatus, Gymnura altavela and Rioraja agassizii, are under some level of risk of extinction, while two others (Rhizoprionodon lalandii and Myliobatis goodei) are listed as Data Deficient. Our results indicate that the commercial exploitation of endemic sharks and rays at risk of extinction is commonplace in southern Brazil. This reinforces the need for more systematic monitoring of the trade in fishery products and more effective application of the environmental legislation and conservation programmes.
Keywords: cação; COI gene; DNA barcode; genetic conservation; mislabelling; overfishing